2012
DOI: 10.1039/c2cc16656a
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate functionalized iron(iii) complexes as biomimetic siderophores

Abstract: Catechol functionalized iron(III) glycodendrimers have been prepared using a self-assembly process for targeting a specific strain of E. coli bacteria and have been shown to exhibit carbohydrate-lectin mediated iron delivery in growth promotion assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…To address the biological significance of glyco‐AuNPs, their binding affinity to ConA lectin was established . We performed inhibition studies for the binding of these lectins to mannose–BSA in the presence of homo‐ and hetero‐glyco‐AuNPs and quantitation was reported as the IC 50 value (Table and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…To address the biological significance of glyco‐AuNPs, their binding affinity to ConA lectin was established . We performed inhibition studies for the binding of these lectins to mannose–BSA in the presence of homo‐ and hetero‐glyco‐AuNPs and quantitation was reported as the IC 50 value (Table and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Pipyridyl‐glycoclusters functionalized with the Tn‐antigen (α‐GalNAc‐OR) were used for the formation of copper(II) complexes with enhanced binding to Vicia villo lectin (R. Roy & Kim, ). Similarly, a catechol‐functionalized iron(III) glycodendrimer better targeted Escherichia coli ORN78 and was used as an iron delivery carrier (Yadav & Kikkeri, ). Saccharide‐coated M 12 L 24 complexes based on Pd(II) (Y. Liu, Zhang, et al, ) showed potential in Alzheimer diagnosis (Sato et al, ; Yan et al, ).…”
Section: Oligosaccharidesmentioning
confidence: 99%
“…To illustrate the first point, abundant examples are available in nature in the form of siderophores such as enterobactin, bacillibactin, and vibriobactin. [26][27][28] Since Fe 3 + is a hard Lewis acidic center, it prefers hard donors such as oxide ions for stabilization. Again, generation of the lowenergy LCMT band in Fe III -catecholate complexes is well documented in the literature.…”
Section: Synthesis and General Aspectsmentioning
confidence: 99%